Community forest management: Can the green economy contribute to environmental justice?. (12th April 2013) - Barkin, David; Fuente, Mario
Abstract: Policymakers face a dilemma in highly diverse societies with many ecosystems: how to implement national policies that allow for serious consideration of these differences. In connection with the attempts to advance towards sustainability in forest systems, Mexico is confronting this problem with difficulty. Although it has committed to implementing policies consistent with REDD +, there are competing pressures for supporting commercial development of plantations on the one hand, and community based management systems that involve multiple objectives in complex proposals on the other. We trace the implications for environmental justice of the choices being made by indigenous communities in the highlands of Oaxaca for promoting sustainable programmes that assure adequate living standards and environmental protection. The analysis shows that this alternative approach offers an interesting set of outcomes that the standard paradigm of the green economy has difficulty achieving.